Identification of a novel enterotoxigenic activity associated with Bacillus cereus. Issue 10 (October 1976) - Melling, J; Capel, B J; Turnbull, P C; Gilbert, R J
Abstract : A strain of Bacillus cereus isolated from a food poisoning outbreak characterized by vomiting has been shown to be capable of causing vomiting when cultures grown on rice, but not other media, were fed to Rhesus monkeys. In contrast, a strain isolated from a diarrhoeal outbreak produced diarrhoea, but not vomiting, when grown on various media in similar feeding trials. Furthermore, culture filtrates from the diarrhoeal strain caused fluid accumulation in ligated rabbit ileal loops whereas those from the vomiting strain did not. It is proposed that at least two enterotoxins are involved, one responsible for the vomiting and one for the diarrhoeal symptoms.